A review of the genus Abdosetae (Araneae: Phrurolithidae) from China - Jin, Chi; Fu, Jianying; Zhang, Feng (Zootaxa, 2015)
Four species of the genus Abdosetae Fu, Zhang & MacDermott, 2010 from China are reviewed, and three of them are new to science: A. digitata sp. nov., A. falcata sp. nov. and A. hamata sp. nov. We re-examined the type material of A. hainan Fu, Zhang & MacDermott, 2010, re-delimited the generic characteristics and re-described the type species. A key to all Abdosetae species and a distribution map of the Chinese species are provided.